Motion Events in L1 and L2 Mapudungun Narratives: Typology and Cross-Linguistic Influence - Becerra, Rodrigo; Osorio, Jorge; Cantarutti, Ítalo; Llanquinao, Gabriel (Frontiers in Communication, 2022)
We compare the motion lexicalization patterns produced by L1 and L2 speakers of Mapudungun, an indigenous minority language spoken in Chile and Argentina. According to previous descriptions, the patterns of motion expression in Mapudungun have some characteristics of an equipollently-framed language, which contrast with the usual motion expression in Spanish. The data for the study was collected using the picture storybook “Frog, where are you?”, considering oral narratives produced by 10 Mapudungun native speakers and 9 Spanish native speakers who are late bilinguals of Mapudungun. We report the general results (comparison of total clauses, translational clauses, types, and tokens) and analyze three general conflation patterns: the encoding of the semantic components of Path and Manner, the conflation of various components into serial verb constructions, and the encoding of Ground. The results show that L1 speakers encoded a significantly higher proportion of Manner verbs and a lower proportion of Path verbs than L2 speakers, use a more diverse inventory of Path and Manner verb types, a significantly higher number of motion serial verb constructions, and a slightly significantly lower number of Ground phrases per clause than L2 speakers, suggesting cross-linguistic influence from Spanish.